Self-Efficacy as a Predictor of Stress in Medical Students of King Khalid University, Saudi Arabia - Siddiqui, Aesha F (UI Scholars Hub, 2018)
Background: Self-efficacy and stress are closely related concepts. These concepts have been endorsed as the primary causes influencing the adaptation of students to the college environment. The objectives of this study were to: 1) Measure self-efficacy among medical students, 2) Study association of self-efficacy with basic characteristics of the students, 3) Determine the role of self-efficacy as a predictor of stress. Methods: Self efficacy and stress were measured using the Kesseler-10 instrument and the General Self Efficacy scale, for 267 medical students, including both sexes. Statistical analysis included descriptive statistics for the basic characteristics and self-efficacy, independent samples t-test and ANOVA to find the association between self-efficacy and various socio-demographic factors and correlation and regression analysis to determine the role of self-efficacy as a predictor of stress. Results: Students aged more than 22 years had significantly higher self–efficacy scores as compared to younger students (t=2.32; p ˂ 0.05). The linear relationship between stress and self-efficacy was demonstrated using Pearson’s correlation. A significant negative correlation was revealed (r = -0.136, R2 = 0.018); p ˂ 0.05. Self efficacy was identified as a predictor of stress. Predicted stress score = 27.91+ (-.165* X). Conclusions: Self efficacy has a significant negative correlation with stress in medical students and is a predictor of stress.